Complete chloroplast genome sequence of historical olive (Olea europaea subsp. europaea) cultivar Mehras, in Jordan. Issue 1 (2nd January 2021) - Haddad, Nizar; Migdadi, Hussein; Brake, Mohammad; Ayoub, Salam; Obeidat, Wisam; Abusini, Yahya; Aburumman, Abeer; Al-Shagour, Banan; Al-Anasweh, Eman; Sadder, Monther
Abstract: The complete chloroplast genome sequence of Olea europaea subsp. europaea cultivar Mehras was determined using high-throughput sequencing technology. Chloroplast genome was 155, 897 bp in length, containing a pair of 25, 742 bp inverted repeat (IR) regions, which were separated by large and small single-copy regions (LSC and SSC) of 86, 622 and 17, 791 bp, respectively. The chloroplast genome contained 130 genes (85 protein-coding, 37 tRNA, and eight rRNA). GC content was 37.8%. We performed phylogenetic analysis with other isolates. The analysis showed that O. e. subsp. europaea cultivar Mehras has an ancient common ancestor with cultivated olives in Italy, Spain, and Cyprus.